The effect of job strain on nighttime blood pressure dipping among men and women with high blood pressure - Lin-Bo Fan; James A Blumenthal; Alan L Hinderliter; Andrew Sherwood (Nordic Association of Occupational Safety and Health (NOROSH), 2013)
OBJECTIVES: Blunted nighttime blood pressure dipping is an established cardiovascular risk factor. This study examined the effect of job strain on nighttime blood pressure dipping among men and women with high blood pressure. METHODS: The sample consisted of 122 blue- and white collar workers (men=72, women=50). The Job Content Questionnaire was used to measure job psychological demands, job control, and social support. The ratio of job demands to job control was used to assess job strain. Nighttime blood pressure dipping was evaluated from 24-hour ambulatory blood pressure monitoring performed on three workdays. RESULTS: Men with high job strain had a 5.4 mm Hg higher sleep systolic blood pressure (P=0.03) and 3.5 mm Hg higher sleep pulse pressure (P=0.02) compared to men with low job strain. Men with high job strain had a smaller fall in systolic blood pressure and pulse pressure from awake to sleep state than those with low job strain (P<0.05). Hierarchical analyses showed that job strain was an independent determinant of systolic blood pressure dipping (P=0.03) among men after adjusting for ethnicity, body mass index, anxiety and depression symptoms, current smoking status, and alcohol consumption. Further exploratory analyses indicated that job control was the salient component of job strain associated with blood pressure dipping (P=0.03). CONCLUSIONS: High job strain is associated with a blunting of the normal diurnal variation in blood pressure and pulse pressure, which may contribute to the relationship between job strain and cardiovascular disease.